Effects of dietary glycyrrhiza polysaccharide on growth, serum biochemistry, and hepatic transcriptome in juvenile chinese sturgeon (Acipenser sinensis) - Jianming Zhang; Tian Tian; Rui He; Binzhong Wang; Wei Jiang; Yacheng Hu (PLoS ONE, 2026)
The Chinese sturgeon ( Acipenser sinensis ), a critically endangered anadromous species, faces severe population declines due to habitat fragmentation and overfishing. This study investigates the effects of dietary Glycyrrhiza polysaccharide (GCP) on growth performance, serum biochemistry, and hepatic transcriptome in juvenile Chinese sturgeon. One hundred and twenty uniform-sized juveniles (365.6 ± 86.4 g, 45.2 ± 4.1 cm) were randomly allocated to four groups (n = 30; 3 × 10 fish). The experiment consisted of a basal diet supplemented with 0.0% (control), 0.5%, 1.0%, or 2.0% GCP. After 36 days of feeding, significant differences in growth performance were observed among the experimental groups. Compared with control, 2% GCP increased final body weight by 13.1% (699.6 ± 45.3 g vs 618.6 ± 27.0 g, P = 0.008) and reduced feed conversion ratio by 18% (1.15 ± 0.06 vs 1.40 ± 0.09, P = 0.003); serum IGF-1 rose 33% (12.52 ± 1.71 vs 9.44 ± 2.37 ng mL ⁻ ¹, P = 0.012). Hepatic transcriptome profiling identified 400 differentially expressed genes (DEGs) between the control and 2.0% GCP groups (214 up-regulated, 186 down-regulated), with pronounced enrichment in pathways governing energy metabolism, lipid biosynthesis, and cellular proliferation. Transcriptomics (|log₂FC| ≥ 1, FDR < 0.01) revealed 400 differentially expressed genes enriched in lipid metabolism and GH-IGF-1 signaling. Key upregulated genes included those involved in lipid synthesis, glycolysis, and growth signaling. The findings demonstrate that dietary supplementation of 2.0% GCP significantly enhances growth performance in juvenile Chinese sturgeon by modulating endocrine signaling and upregulating metabolic pathways, providing a molecular foundation for GCP’s role in improving aquaculture productivity and conservation strategies.